Health Policy Challenge for Breast Cancer Prevention: A Case Report (Unnes Journal of Public Health, 2021)
Breast cancer early diagnosis increases treatment chances, and self-examination is one of the commonest screening methods employed by women. The case of a 24-year-old Iranian woman with a history of mild mental retardation and chest pain was reported. A large lump was detected in the breast during visitation to the surgical clinic. The parents stated the lump was noticed due to a shape change in the clothes covering the patient's chest area. Therefore, the patient had mastectomy surgery after a biopsy and a malignant breast lump was confirmed. The registration and identification of people with mental disorder histories or various mental retardation degrees in each region's health centers to periodically assess their breast health tend to reduce the risk of late breast cancer detection in women.